2019
DOI: 10.1016/j.ultrasmedbio.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Acoustic Emissions from Therapeutically Driven Contrast Agent Microbubbles

Abstract: Non-linear emissions from microbubbles introduced to the vasculature for exposure to focused ultrasound are routinely monitored for assessment of therapy and avoidance of irreversible tissue damage. Yet the bubble-based mechanistic source for these emissions, under subresonant driving at typical therapeutic pressure amplitudes, may not be well understood. In the study described here, dual-perspective high-speed imaging at 210,000 frames per second (fps), and shadowgraphically at 10 Mfps, was used to observe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
5
27
1
Order By: Relevance
“…Microbubbles (MBs) are considered to play a major role in increasing permeabilization of various drugs through the cell membrane and into the cytoplasm (Tachibana et al, 1999). Recent experiments using high speed video cameras under optic microscopes have shown that oscillation of MBs during US irradiation actually disrupts the cell membrane to form transient pores (Kudo et al, 2009;Nejad et al, 2016;Song et al, 2019). This phenomenon, frequently referred as sonoporation (Lammertink et al, 2015), induces increase in cell uptake of administrated drugs, molecules, and in some cases plasmid DNA (Sennoga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microbubbles (MBs) are considered to play a major role in increasing permeabilization of various drugs through the cell membrane and into the cytoplasm (Tachibana et al, 1999). Recent experiments using high speed video cameras under optic microscopes have shown that oscillation of MBs during US irradiation actually disrupts the cell membrane to form transient pores (Kudo et al, 2009;Nejad et al, 2016;Song et al, 2019). This phenomenon, frequently referred as sonoporation (Lammertink et al, 2015), induces increase in cell uptake of administrated drugs, molecules, and in some cases plasmid DNA (Sennoga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental arrangement is fully described in Song et al (2019) and is represented schematically in Figure 1. Briefly, a polycarbonate capillary 500 μm in internal diameter and 25 μm wall thickness (Paradigm Optics, Vancouver, WA, USA) was positioned at 45° to the propagation axis of a focused ultrasound transducer, horizontally across the focal region.…”
Section: Methodsmentioning
confidence: 99%
“…Illumination was achieved with synchronous (to frame capture) 10-ns laser pulses, coupled to a liquid light guide and a collimator lens. Other than the focused ultrasound driving f 0 of 200 kHz used here, the only other difference to the configuration previously described (Song et al 2019) is that side-view imaging for this work was conducted through a 20 × long-working-distance objective lens (0.42 NA, Mitutoyo), at a higher spatial resolution of ∼ 1.1 μm/pixel but over a reduced FOV, represented by the solid rectangle in the xy plane (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most needle hydrophones use PVDF as the active element, not only because of its broadband frequency response, its acoustic impedance close to water, and its good receiving sensitivity [28][29][30], but also because of its accessibility and affordability. When placed close to a single microbubble, they have been proven to capture the unique shock waveforms that bubble collapse generates [18,31,32]. More recently, a study investigated the use three hydrophones to localize cavitation activity [33].…”
Section: Passive Cavitation Detection With a Needle Hydrophone Arraymentioning
confidence: 99%